IS URBANISATION SANS INFRASTRUCTURE A MYTH? EVIDENCE FROM INDIA - Arora, Rochna; Kaur, Baljit (Economic Annals, 2022)
This study examines the determinants of urbanisation in Indian states with special emphasis on infrastructure and infrastructure investment, using data on 17 Indian states for 1991 to 2017. The fixed effects regression model shows that physical infrastructure is an important determinant in high income states, while social infrastructure is important in high-income and low-income states (where the magnitude is negative). Electricity consumption and teledensity positively affect urbanisation in high- and low-income states, while the infant mortality rate in high-income states and the enrolment ratio in low-income states affect urbanisation negatively. The supply-led inverted-U hypothesis of infrastructure-investment-led urbanisation is only disproven for middle-income states while applying strongly in all other cases, particularly low-income states. Hence, the impact of infrastructure on urbanisation differs across states not only by type of infrastructure but also by the state’s income category.